An Overview of Service Delivery and Customer Satisfaction in the Telecommunications Industry in Nigeria - J. O., Adetayo; Apollos, Emerah Ajevata (Indian Journal of Marketing, 2013)
The study examined service delivery and customer satisfaction in the telecommunications industry in Nigeria. The study assessed the level of satisfaction of GSM subscribers and the discrepancies (if any) in the level of satisfaction among them. Data were collected using a structured questionnaire distributed to four hundred respondents in Lagos and Oyo states of Nigeria. Descriptive statistics such as frequency, percentages, weighted mean as well as inferential statistics such as analysis of variance (ANOVA) were used for analyzing the variables of interest. The results obtained showed a general mean of 3.66 on a 5-point Likert scale. This means that the customers were satisfied with the services of the GSM operators operating in the mobile telecommunications industry in Nigeria. It is recommended that players in the mobile telecommunications industry should strive to raise the level of customer satisfaction by focusing on courtesy and upgrading of their operational facilities in order to widen their coverage area. Also, regulatory authorities, especially the Nigerian Communication Commission (NCC), should step up the level of supervision, while the Government should register and grant licenses to more mobile telecommunication companies to increase competition in the industry.